2022
DOI: 10.3389/fphys.2022.964887
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the role of mast cells in the progression of liver disease

Abstract: In addition to being associated with allergic diseases, parasites, bacteria, and venoms, a growing body of research indicates that mast cells and their mediators can regulate liver disease progression. When mast cells are activated, they degranulate and release many mediators, such as histamine, tryptase, chymase, transforming growth factor-β1 (TGF-β1), tumor necrosis factor–α(TNF-α), interleukins cytokines, and other substances that mediate the progression of liver disease. This article reviews the role of ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 104 publications
0
4
0
Order By: Relevance
“…The results of our study also revealed that the HRG, characterized by a poor prognosis, exhibited elevated levels of macrophage M0 infiltration. In addition, mast cells can facilitate the onset and progression of HCC by increasing the population of immunosuppressive cells, resulting in a poor prognosis ( 64 ). In our study, we found that the HRG had a lower proportion of mast cells in a resting state.…”
Section: Discussionmentioning
confidence: 99%
“…The results of our study also revealed that the HRG, characterized by a poor prognosis, exhibited elevated levels of macrophage M0 infiltration. In addition, mast cells can facilitate the onset and progression of HCC by increasing the population of immunosuppressive cells, resulting in a poor prognosis ( 64 ). In our study, we found that the HRG had a lower proportion of mast cells in a resting state.…”
Section: Discussionmentioning
confidence: 99%
“…Mast cell activation and degranulation were among the highest upregulated GOBP terms. Interestingly, recent studies suggested that mast cells play a significant role in the progression of various liver diseases ( 47 ). The major proteins driving liver inflammation in Lal−/− mice included PLD3, ANXA1, and CHIL3.…”
Section: Discussionmentioning
confidence: 99%
“…These cells express multiple PRRs that allow them to respond to diverse stimuli and release several cytokines, such as TNF-α, TGF-β, and ILs. MCs can lead to microvesicular steatosis, ductal reaction, biliary senescence, inflammation, angiogenesis, and liver fibrosis during MAFLD/NAFLD/NASH [ 67 ] ( Fig. 1 ).…”
Section: Innate-like T Cellsmentioning
confidence: 99%